ELib on datagrid a search application for geographically separated resources using the data grid - Baldenero, Oliver T. (2005)
A Data Grid is set of systems and applications that are able to provide a multitude of qualities yet appear as a single entity to a user. The main goal of a Data Grid is to combine information from multiple sources of data and provide a single point of access for the user. low end commodity computers are combined with multiple servers and Grid enabling software to form the Data Grid. ELib on DataGrid is a search application for geographically separated resources using the Data Grid. Users are able to search through the content and tags of a PDF of text document, even if these files are located on different servers at different locations. Additional processing can also be done, as users are able to search on the results returned by the application. In searching and accessing data from the Grid, there are three issues that we need to concern ourselves with: Transparency, Security and Accessibility. We need to abstract the Grid from the users, so as to make it look like the user is only accessing a single server. Transparency is an important aspect of our Data Grid architecture, since this is needed to enable optimization across diverse, distributed resources and to keep the application more manageable. Also, we need to make sure that unknown or anonymous users won't be able to tamper with the main data stored on the servers and at the same time, they would be able to access relevant data in the most efficient way. Security is important so as to prevent possible intruders and unauthorized users to view sensitive data. Accessibility is equally important because users want to be able to access and retrieve data in a fast, efficient way even if these data are not within the same vicinity or even the same country as they are.